The Cheyenne - Santella, Andrew (New York Children's Press, 2002)
Describes the Cheyenne way of life, including their traditions, customs, buffalo hunts, leaders, and land
Includes bibliographical references (p. 44) and index
Hurg
5 8
Keywords: Cheyenne Indians -- History; Cheyenne Indians -- Social life and customs; Indians of North America -- Great Plains